Flumazenil may improve gait and mentation in dogs presenting with marijuana toxicosis - Fitzgerald, Alyson H.; Zhang, Yuntao; Stewart, Samuel; Fritz, Scott A.; Lynch, Alex M.; Ramras, Monique; Meola, Stacy D. (Frontiers in Veterinary Science, 2024)
IntroductionAlongside the United States’ growing landscape of legalized recreational marijuana intended for humans, cases of canine marijuana toxicosis have been on the rise. Most commonly these dogs have mild clinical signs and respond well to supportive therapies. However, patients might still be ataxic, unable to walk, or remain heavily sedated at the time of discharge. Our hypothesis was that flumazenil would improve the level of consciousness, brainstem reflexes, gait, and stance in dogs with marijuana toxicosis.MethodsSeventeen dogs presenting for marijuana toxicosis were enrolled. MGCS and Canine Marijuana Severity Score (CMSS), were used to assess level of consciousness, brain stem reflexes, gait, and stance. Flumazenil 0.01 mg/kg was administered IV once. Baseline values immediately before flumazenil administration, 5 min, 15 min, and 30 min after flumazenil were recorded. Serum was collected and analyzed for delta-9-THC using ultraperformance liquid chromatography.ResultsThere was a significant change in MGCS and CMSS following flumazenil administration (p = 0.0033 and p ≤ 0.001). The median CMSS at baseline was 17 (10–19), at 5 min was 18 (10–21), at 15 min was 18 (12–22), and at 30 min was 19 (14–22). There was a significant difference between the concentration of delta-9-THC and clinical sign score (p = 0.0275).DiscussionThe administration of flumazenil to dog affected by marijuana toxicosis might result in improved gait, stance, and level of consciousness. There might be some discriminative ability of the CMSS to stratify the severity level of canine marijuana toxicosis.